S-Nitrosation of arginase 1 requires direct interaction with inducible nitric oxide synthase - Dunn, Jessilyn (2011)
Arginase constrains endothelial nitric oxide synthase activity by competing for the common substrate, L-Arginine. We have recently shown that inducible nitric oxide synthase (NOS2) S-nitrosates and activates arginase 1 (Arg1) leading to age-associated vascular dysfunction. Here, we demonstrate that a direct interaction of Arg1 with NOS2 is necessary for its S-nitrosation. The specific domain of NOS2 that mediates this interaction is identified. Disruption of this interaction in human aortic endothelial cells prevents Arg1 S-nitrosation and activation. Thus, disruption of NOS2–Arg1 interaction may represent a therapeutic strategy to attenuate age related vascular endothelial dysfunction.